A novel fog-cloud architecture to process serverless functions with adaptive timeout - Cassel, Gustavo André Setti; Righi, Rodrigo da Rosa; Rodrigues, Vinicius Facco (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2022)
This paper presents a novel architecture to handle serverless functions with adaptive timeout, leveraging prediction to foresee how long the incoming request will take to finish based on historical data. This decision-making process aims to ensure that no request will be discarded, while maximizing execution throughput and offloading requests from the fog to the cloud when needed.